Efficient welding method

By adopting the bevel welding process and new low-carbon and low-alloy welding wire during the welding process of P690QL2 steel, combined with preheating, inter-channel temperature control and slow-cool welding post-treatment, the problem of insufficient low-temperature toughness and impact resistance of the welded joints is solved. Welded joints with high strength and excellent low temperature performance are achieved.

CN119387772AActive Publication Date: 2025-02-07CHINA IRON & STEEL RESEARCH INSTITUTE GROUP CO LTD
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202411723970.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-02-07
Estimated Expiration
2044-11-28

AI Technical Summary

Technical Problem

The existing welding process is prone to defects such as thermal cracks, pores, and coarse crystallization in the high-strength material P690QL2 steel, resulting in poor low-temperature toughness and impact resistance of weld metals, making it difficult to meet the special needs of liquefied carbon dioxide storage tanks.

Method used

The bevel welding process is adopted. The direction of the adjacent welding layer is opposite, and the direction of the same welding layer is the same. New low-carbon and low-alloy welding wire is used to preheat and inter-channel temperature control are used during welding, and slow cooling is used after welding. After welding is processed.

Benefits of technology

It effectively reduces the risk of cracks during welding, and the weld metal formed has high strength, excellent low-temperature toughness and impact resistance, meeting the needs of liquefied carbon dioxide storage tanks under high-pressure and low-temperature extreme environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119387772A_ABST
    Figure CN119387772A_ABST
Patent Text Reader

Abstract

The invention relates to an efficient welding method, belongs to the technical field of welding processes, and solves the problems that the defects of hot cracks, air holes, coarse crystallization and the like are easily generated when a high-strength material is welded by an existing welding process, and the strength and low-temperature toughness of weld metal are insufficient. The invention provides an efficient welding method which adopts a groove welding process, the welding bead directions of adjacent welding layers are opposite, and the welding bead directions of the same welding layer are the same; according to the welding method, a low-carbon low-alloy welding wire is adopted, and the welding wire comprises the following components in percentage by mass: 0.04 to 0.08 percent of C, 0.30 to 0.50 percent of Si, 1.6 to 2.0 percent of Mn, 0.15 to 0.35 percent of Cr, 3.5 to 4.0 percent of Ni, 0.008 to 0.01 percent of Cu, 0.007 to 0.01 percent of Mo, 0.0005 to 0.001 percent of V, 0.02 to 0.07 percent of Ti and 0.01 to 0.018 percent of Al. The efficient welding method is suitable for welding of P690QL2 steel, and the mechanical property and the low-temperature toughness of a welded joint are remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of welding technology, and in particular to a high-efficiency welding method. Background Art

[0002] As the global demand for storage and transportation of liquefied carbon dioxide continues to increase, cryogenic and high-pressure storage tanks have become key equipment. However, the materials currently used for liquefied carbon dioxide storage tanks are mostly steels with relatively low yield strength, such as 07MnNiMoVDR (yield strength 490MPa) and 15MnNbR (yield strength 370MPa). Although these materials can meet the needs of ordinary cryogenic storage tanks, they often show shortcomings under high-pressure and low-temperature extreme conditions such as liquefied carbon dioxide storage tanks, such as limited strength and unsatisfactory impact resistance, which makes it difficult for the tank's load-bearing capacity and safety to reach the optimal state.

[0003] In order to achieve a higher storage capacity per unit volume of storage tanks, it is inevitable to use materials with higher strength levels. 690MPa-grade high-strength low-temperature steel P690QL2 has become one of the ideal materials for the manufacture of liquefied carbon dioxide storage tanks due to its excellent low-temperature toughness and high strength performance. The use of P690QL2 steel can effectively reduce the wall thickness of the storage tank and reduce the weight of the structure, thereby improving the storage efficiency and economic benefits of the storage tank without increasing the cost. In addition, the use of this high-strength material gives the storage tank a higher safety margin when facing high-pressure conditions.

[0004] However, the technical challenges of P690QL2 steel in the welding process are significant. Due to the high strength characteristics of the material, defects such as thermal cracks, pores, and coarse graining are easily generated during welding, which will affect the toughness and mechanical properties of the welded joint, especially the impact resistance in low temperature environments. The low-temperature toughness and impact resistance of the weld metal formed by the existing process are poor, which is difficult to meet the special needs of liquefied carbon dioxide storage tanks. Summary of the invention

[0005] In view of the above analysis, an embodiment of the present invention aims to provide an efficient welding method to solve at least one of the problems that the existing welding process is prone to produce defects such as thermal cracks, pores, coarse graining, etc. when working with high-strength materials (especially P690QL2 steel) and the low-temperature toughness and impact resistance of the weld metal are poor.

[0006] The present invention provides an efficient welding method, wherein the welding method adopts a groove welding process, the welds of adjacent weld layers are in opposite directions, and the welds of the same weld layer are in the same direction;

[0007] The welding method adopts a new type of low-carbon low-alloy welding wire, and the components in the welding wire are calculated by mass percentage: C 0.04-0.08%, Si 0.30-0.50%, Mn 1.6-2.0%, Cr 0.15-0.35%, Ni 3.5-4.0%, Cu 0.008-0.01%, Mo 0.007-0.01%, V 0.0005-0.001%, Ti 0.02-0.07%, Al 0.0.01-0.018%.

[0008] The welding method comprises the following steps:

[0009] S1: Open the groove according to the material and specifications of the welded parts;

[0010] S2: MAG welding is used to weld layers one by one. The welding direction is adjusted after each layer is welded. The welding directions of adjacent layers are opposite, while the welding directions of the same layer are the same.

[0011] S3: After welding is completed, post-weld treatment is performed.

[0012] Specifically, the welded parts are preheated before welding, and the preheating temperature is 100-120°C; during the welding process, the interpass temperature is controlled at 100-120°C.

[0013] Specifically, the composition of the shielding gas for MAG welding in step S2 is 95% argon + 5% carbon dioxide (volume ratio).

[0014] Specifically, the flow rate of the protective gas is controlled at 18-22 L / min.

[0015] Specifically, the specific process parameters of step S2 are: welding current is 310-340A, welding voltage is 31-33V, welding speed is 40-44cm / min, and heat input is controlled at 14-16KJ / cm.

[0016] Specifically, the post-weld treatment is performed by a heat preservation and slow cooling method.

[0017] Specifically, the welding method is suitable for welding P690QL2 steel.

[0018] Specifically, the weld metal microstructure formed by the welding method is ferrite and bainite; the relative ratio (volume ratio) of the two is bainite:ferrite=0.80-0.85:0.15-0.20, and the grain size is 1.70-1.80 μm.

[0019] Furthermore, the yield strength of the welded joint formed by the welding method is ≥792MPa, the tensile strength is ≥894MPa, and the elongation is ≥13.5%; the average absorbed energy of the -60°C impact test is ≥130.4J, and the joint hardness is 315-367HV.

[0020] Compared with the prior art, the present invention can achieve at least one of the following beneficial effects:

[0021] 1. The welding method provided by the present invention is not prone to cracks during the welding process. During the welding process, the welding direction is adjusted after each weld pass is completed to avoid the concentration and cumulative effect of thermal stress caused by continuous welding, thereby effectively reducing the risk of welding cracks.

[0022] 2. The present invention adopts a new type of low-carbon low-alloy welding wire for welding, and the formed weld has good matching with high-strength steel (especially P690QL2 steel), and has excellent mechanical properties and low-temperature toughness.

[0023] The compatibility of the new low-carbon low-alloy welding wire used in the present invention with P690QL2 steel is mainly reflected in the following aspects:

[0024] Component compatibility: The chemical composition of the welding wire has good compatibility with the chemical composition of P690QL2 steel. For example, the high content of Ni and Mo in the welding wire forms a good combination with the corresponding elements of the base material, improves the bonding strength of the interface between the weld and the base material, and reduces the interface defects caused by chemical mismatch. Matching of thermal expansion coefficient: The thermal expansion coefficient of the welding wire is close to that of P690QL2 steel, which can reduce residual stress during the cooling process after welding and reduce the risk of cracks in the weld area. Matching of mechanical properties: The yield strength (Rp0.2) of P690QL2 steel is ≥690MPa, and the tensile strength (Rm) is 770-940MPa. The yield strength (≥792MPa) and tensile strength (≥894MPa) of the joint formed after welding by the welding method of the present invention match the strength of the base material, thereby ensuring the load-bearing capacity of the weld area in actual use.

[0025] Excellent mechanical properties of weld metal:

[0026] The role of Ni (nickel): The Ni content in the welding wire is 3.5%-4.0%, which forms fine and uniform acicular ferrite and bainite structures in the weld, improving the strength and low-temperature toughness of the weld metal. Ni also reduces grain boundary segregation and enhances the impact resistance of the weld. The role of Mo (molybdenum): The Mo content is 0.007%-0.01%, which can effectively prevent the grain growth of the weld structure, improve the toughness in low-temperature environments, and enhance the wear resistance and corrosion resistance of the weld. The role of Ti (titanium): The Ti content is 0.02%-0.07%, which can refine the weld grains, form a uniform fine-grained structure, and improve the mechanical properties and toughness of the joint. The role of Mn (manganese): The Mn content is 1.6%-2.0%, which can effectively improve the strength and toughness of the weld metal, and reduce the thermal crack sensitivity of the weld by combining with S (sulfur) to form MnS inclusions. Function of Al (aluminum): The Al content is 0.01%-0.018%, which has the effect of deoxidation and grain refinement, and improves the toughness and impact resistance of the weld.

[0027] In summary, the welding wire design and process control in the present invention ensure high matching between the weld and P690QL2 steel, thereby forming a high-strength, high-toughness welded joint that meets the use requirements of liquefied carbon dioxide storage tanks under high pressure and low temperature extreme environments. The welded joint formed by the welding method has a yield strength of ≥792MPa, a tensile strength of ≥894MPa, and an elongation of ≥13.5%; the average absorbed energy of the -60℃ impact test is ≥130.4J, and the joint hardness is 315-367HV.

[0028] 3. The welding method provided by the present invention innovatively uses 95% argon + 5% carbon dioxide shielding gas instead of the traditional 80% argon + 20% carbon dioxide. This gas ratio significantly reduces the formation of pores and inclusions, improves the weld metal structure, and makes the weld joint have higher strength and low-temperature toughness by increasing the penetration and stability of the welding zone.

[0029] 4. The welding method provided by the present invention adopts a slow cooling method to control the cooling rate after welding. Compared with post-weld heat treatment, the present invention can prevent the weld structure from becoming brittle and ensure the excellent toughness of the weld joint under low temperature conditions.

[0030] 5. The welding method provided by the present invention has simple process, low cost, excellent comprehensive performance of the welded joint, and is suitable for large-scale promotion.

[0031] In the present invention, the above-mentioned technical solutions can also be combined with each other to achieve more preferred combination solutions. Other features and advantages of the present invention will be described in the subsequent description, and some advantages can become obvious from the description, or can be understood by practicing the present invention. The purpose and other advantages of the present invention can be realized and obtained through the contents particularly pointed out in the description and the drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] The drawings are only for the purpose of illustrating particular embodiments and are not to be considered limiting of the present invention. Like reference symbols denote like components throughout the drawings.

[0033] Figure 1 This is a metallographic photograph of the weld metal in Example 1;

[0034] Figure 2 This is a metallographic photograph of the weld metal in Comparative Example 1;

[0035] Figure 3 This is a photo of the weld morphology in Example 1. DETAILED DESCRIPTION

[0036] The preferred embodiments of the present invention are described in detail below in conjunction with the accompanying drawings, wherein the accompanying drawings constitute a part of this application and are used together with the embodiments of the present invention to illustrate the principles of the present invention, but are not used to limit the scope of the present invention.

[0037] After extensive research and theoretical analysis, the following problems were found in the existing welding process:

[0038] (1) Insufficient strength of welded joints: The high strength characteristics of P690QL2 steel make it easy to produce cracks and defects during welding, resulting in the tensile strength and yield strength of the joint failing to meet the parent material standards.

[0039] (2) Poor low-temperature toughness: Traditional shielding gases (such as 80% Ar + 20% CO2) can easily cause the weld metal grains to coarsen, and the low-temperature impact resistance of the welded joint does not meet the standards, making it difficult to meet the requirements for the use of liquefied carbon dioxide storage tanks in low-temperature environments.

[0040] (3) Stress concentration problem: The existing welding process lacks optimized design for welding direction and sequence, which leads to stress concentration during welding and easily induces cracks.

[0041] The present invention provides an efficient welding method, which adopts a groove welding process, wherein the welds of adjacent weld layers have opposite directions, and the welds of the same weld layer have the same direction; by changing the welding direction of adjacent weld layers, the stress concentration generated during the welding process is reduced, the generation of cracks is prevented, and the strength and toughness of the joint are improved. During the welding process, the same direction of the welds of the same weld layer can ensure uniform heat input, reduce the risk of cracks caused by thermal stress concentration, and optimize the fluidity of the molten pool, reduce the generation of defects such as pores and slag inclusions, and improve the forming quality of the weld and the uniformity of the microstructure. In addition, this method can make the mechanical properties of the weld metal more stable, avoid stress concentration and uneven grains caused by direction switching, and thus enhance the strength and toughness of the welded joint. This operation is not only convenient for the stability control of manual welding, but also helps automated welding equipment to improve welding efficiency and quality, and is particularly suitable for the welding needs of high-strength low-temperature steel.

[0042] The welding method adopts a new type of low-carbon low-alloy welding wire, and the components in the welding wire are calculated by mass percentage: C 0.04-0.08%, Si 0.30-0.50%, Mn 1.6-2.0%, Cr 0.15-0.35%, Ni 3.5-4.0%, Cu 0.008-0.01%, Mo 0.007-0.01%, V 0.0005-0.001%, Ti 0.02-0.07%, Al 0.01-0.018%.

[0043] Preferably, the components in the welding wire are calculated by mass percentage as follows: C 0.04-0.06%, Si 0.35-0.45%, Mn 1.75-1.85%, Cr 0.25-0.30%, Ni 3.6-3.8%, Cu 0.008-0.01%, Mo 0.007-0.01%, V 0.0005-0.001%, Ti 0.04-0.06%, and Al 0.013-0.015%.

[0044] More preferably, C: 0.051%, Si 0.39%, Mn 1.81%, Cr 0.28%, Ni 3.77%, Cu 0.0097%, Mo 0.0092%, V 0.0006%, Ti 0.055%, Al 0.013%.

[0045] C (Carbon, 0.04-0.08%): Carbon is an important element to enhance the strength of the weld. With an appropriate amount of carbon content, a trace amount of carbides can be formed in the weld metal to enhance its hardness and strength. Controlling the carbon content within this range can not only ensure the strength of the weld, but also avoid brittleness and crack tendency caused by excessive carbon content.

[0046] Si (silicon, 0.30-0.50%): As a deoxidizer, silicon can effectively remove oxygen from the molten pool during welding and improve the purity of the weld metal. In addition, an appropriate amount of silicon helps to improve the tensile strength and plasticity of the weld.

[0047] Mn (manganese, 1.6-2.0%): Manganese has a good desulfurization effect and can form MnS inclusions with sulfur, reducing the embrittlement effect of sulfur on the weld metal and significantly reducing the risk of welding hot cracks. High content of manganese can also improve the strength and toughness of the weld, especially in low temperature environment.

[0048] Cr (chromium, 0.15-0.35%): The addition of chromium can enhance the corrosion resistance of the weld metal. At the same time, during the welding cooling process, chromium helps to form a stable ferrite structure, thereby improving the oxidation resistance and toughness of the weld.

[0049] Ni (nickel, 3.5-4.0%): Nickel is an important element for enhancing the low-temperature toughness and strength of welds, and has significant performance advantages in low-temperature environments. The addition of nickel can also refine the weld structure, reduce grain boundary segregation, and improve the plasticity and impact properties of the weld.

[0050] Cu (copper, 0.008-0.01%): trace copper can enhance the crack resistance of weld metal and help improve the corrosion resistance of weld. The copper content is controlled within a lower range to prevent it from forming harmful low melting point phases during high temperature welding.

[0051] Mo (Molybdenum, 0.007-0.01%): The addition of Mo can refine the grains and enhance the strength and wear resistance of the weld. At the same time, Mo can also reduce the grain growth phenomenon at high temperatures, thereby improving the thermal stability of the weld.

[0052] V (vanadium, 0.0005-0.001%): trace vanadium can significantly refine the weld structure and improve the yield strength and impact resistance of the weld metal. Vanadium can also combine with carbon to form vanadium carbide, further improving the strength and toughness of the weld.

[0053] Ti (titanium, 0.02-0.07%): Titanium is an efficient grain refining element that can significantly improve the low-temperature impact performance of the weld. Titanium can also combine with oxygen to form TiO2 during the welding process, further improving the crack resistance of the weld metal.

[0054] Al (aluminum, 0.01-0.018%): Aluminum is an important deoxidizing element that can improve the purity of weld metal and refine grains. Trace amounts of aluminum can also stabilize the weld structure and enhance the toughness and impact resistance of the weld.

[0055] Synergy:

[0056] Organization optimization: The interaction between Ni, Mo and Ti in the welding wire can promote the formation of acicular ferrite and bainite in the weld, thereby improving the strength and toughness of the weld. Improved crack resistance: The synergistic effect of Mn, V and Cr can significantly reduce the tendency of thermal cracks and pores during welding, making the weld denser and more uniform. Low-temperature performance: Ni, Ti and Al jointly optimize the microstructure of the weld, giving the weld better impact resistance in low-temperature environments. Grain refinement: Ti and V can form stable carbides or nitrides during welding, effectively refining the weld metal grains and improving the overall performance of the weld. Corrosion resistance: The synergistic effect of Cr and Cu can significantly enhance the corrosion resistance of the weld metal in harsh environments.

[0057] Through the precise control and synergistic effect of the above elements, the welding wire can form uniform and fine ferrite and bainite structures during the welding process, so that the weld metal has high strength, high toughness and excellent low-temperature properties, meeting the use requirements of P690QL2 steel under extreme working conditions.

[0058] Specifically, the preparation method of the welding wire is:

[0059] S21 ultra-pure smelting: Preliminary weighing and mixing of raw materials according to preset formula, using double melting technology, first melting in an arc furnace, then refining in an induction furnace to further reduce the content of phosphorus (P) and sulfur (S). The refining temperature is controlled at 1600-1700℃, and the maintenance time is 1.5-3 hours to ensure that impurities are fully floated; the vacuum degree is maintained at least 10^-3Torr during the refining process to avoid oxidation of components or mixing of gas impurities.

[0060] S22 Forging and Rolling:

[0061] During the forging process, the gradual cooling technology is used to control the cooling rate to prevent the internal stress concentration of the material. Each forging application pressure is ≥120MPa to ensure the uniformity and density of the material.

[0062] Specifically, the gradual cooling technology ensures the uniformity of the alloy's structure and grain refinement in different temperature ranges by carefully controlling the cooling rate during forging and rolling. The forging process first preheats the alloy to 850-1050°C, and then forges it at an initial forging temperature of 1150-1250°C, using the gradual cooling technology for temperature control. In the initial stage, a slower cooling rate (30-50°C / h) is used to ensure the plasticity of the alloy and avoid cracks; the cooling rate is further reduced in the medium and low temperature stages (20-40°C / h and 10-20°C / h) to prevent grain coarsening and internal stress concentration. After forging, the alloy should not be cooled quickly immediately, but should be cooled slowly until about 900°C. During this process, direct exposure to the air should be avoided to prevent stress concentration or cracks caused by excessively high or low temperatures. To ensure the uniformity of the material, cooling should be carried out in a controlled environment as much as possible to avoid stress unevenness caused by environmental differences.

[0063] Specifically, the rolling process begins after forging is completed. In the rough rolling stage, the billet is first heated to 1100-1150°C for preliminary deformation and gradual thinning. During this process, the reduction of each rough rolling should be controlled between 25% and 35%, and the cooling rate is 40-60°C / h to prevent surface cracks caused by excessive cooling. The temperature control in the finishing stage is relatively strict, requiring the temperature to be maintained between 850 and 900°C, and the cooling rate to be controlled at 10-20°C / h to ensure grain refinement and uniform structure. During the finishing process, the reduction of each finishing rolling should be controlled between 10% and 15% to maintain the surface quality of the alloy and optimize the mechanical properties. After rolling, the alloy should continue to be cooled evenly to avoid internal stress or cracks caused by excessive temperature difference, and finally obtain high-quality and uniformly structured alloy materials. Through this optimized step-by-step cooling method, problems such as cracks, grain coarsening and internal stress concentration caused by excessive cooling can be effectively avoided, and the mechanical properties and structural uniformity of the alloy can be improved.

[0064] S23 bright drawing: lubricant is added during the drawing process to reduce friction and improve surface finish. Select a synthetic lubricant with stable performance, suitable for high temperature and high tension conditions. The drawing speed is controlled at 5-10m / min to ensure the stability of the material during the drawing process.

[0065] S24 Surface Wiping Cleaning: Use highly absorbent microfiber cloth for mechanical wiping to improve cleaning efficiency. Perform ultrasonic cleaning after mechanical wiping to remove microscopic impurities. The ultrasonic frequency is 35-45kHz, and the cleaning time is 10-20 minutes to completely remove all attached impurities.

[0066] The preparation method of the welding wire adopts ultra-pure smelting technology, strictly controls the content of impurity elements (such as P, S), and reduces the intrusion of gas elements (H, O, N) through vacuum melting and refining deoxidation process to ensure the purity of the welding wire. At the same time, alloy elements (such as C, Ni, Mn, Ti, Mo, etc.) are accurately added according to the designed proportion to achieve component homogenization, further improving the low-temperature toughness and crack resistance of the welding wire. The grains are refined through forging, rolling and bright drawing processes, and combined with surface pickling and cleaning treatment, it is ensured that the surface of the welding wire is free of impurities and pollutants, providing an excellent material basis for high-strength welding.

[0067] Furthermore, after the welding wire is prepared, vacuum annealing technology is used to reduce the diffusible hydrogen content to prevent the occurrence of cold cracks, and the welding wire is stored in a dry or vacuum environment to ensure the long-term stability of the welding wire. The welding wire prepared by this method has high strength, high toughness and low impurity content, which can meet the use requirements of high-pressure and low-temperature equipment such as liquefied carbon dioxide storage tanks, and effectively improve the purity, impact resistance and structural reliability of the weld.

[0068] It is worth emphasizing that the performance of welding wire is mainly determined by the composition design. The preparation process can help improve its performance, but the impact is relatively limited, because the welding wire will actually go through the process of melting and cooling and solidification again during the welding process, and finally form a "new welding alloy / metal". The performance of this "new welding alloy / metal" plays a decisive role in the final welding performance. In other words, the most critical role of the welding wire preparation process is to improve the purity and uniformity of the welding wire as much as possible, remove impurities in it, and then make the performance of the "new welding alloy / metal" more superior.

[0069] Specifically, the welding wire is stored in a vacuum before welding to prevent oxidation from affecting the welding quality.

[0070] The welding method comprises the following steps:

[0071] S1: According to the material and specifications of the welded parts, grooves are opened according to implementation needs and relevant standards;

[0072] S2: MAG welding is used to weld layers one by one. The welding direction is adjusted after each layer is welded. The welding directions of adjacent layers are opposite, while the welding directions of the same layer are the same.

[0073] S3: After welding is completed, post-weld treatment is performed.

[0074] Specifically, the welded parts are preheated before welding, and the preheating temperature is 100-120° C.; the interpass temperature during welding is controlled at 100-120° C. To ensure the temperature consistency during welding, prevent grain coarsening or stress concentration caused by overheating or overcooling in the weld area, and ensure the excellent performance of the welded joint.

[0075] Specifically, the composition of the shielding gas for MAG welding in step S2 is 95% argon + 5% carbon dioxide (volume ratio). As an inert gas, argon can effectively inhibit the oxidation reaction generated during welding, reduce grain boundary inclusions, and improve the purity of the weld metal, thereby improving the low-temperature toughness of the weld. A lower proportion of carbon dioxide provides a certain arc stability while reducing the influence of oxygen content on the organization, forming a fine and uniform grain structure.

[0076] Furthermore, the weld structure with a shielding gas ratio of 95% argon + 5% carbon dioxide is mainly composed of acicular ferrite, side lath ferrite and granular bainite, with uniform tissue distribution and fine grains. A higher proportion of argon as an inert gas can effectively inhibit the oxidation reaction during welding, reduce the oxygen content in the weld metal, and reduce the formation of oxide inclusions at the grain boundaries. This gas ratio promotes a more ideal microstructure transformation process during the cooling process. The high proportion of argon provides a moderate cooling rate, first forming acicular ferrite and side lath ferrite, and then precipitating granular bainite in a lower temperature zone. The moderate cooling rate helps to form a stable bainite phase, ensuring the uniform dispersion and precipitation of carbon in the ferrite, thereby giving the weld a higher strength. The high proportion of bainite and the uniformly distributed ferrite together improve the strength and toughness of the weld, making it show excellent performance in low-temperature impact tests. The fine-grained, multi-phase microstructure effectively disperses stress concentration, reduces the risk of brittle fracture, and significantly improves the overall mechanical properties of the weld joint.

[0077] Specifically, the flow rate of the shielding gas is controlled at 18 to 22 L / min, such as 18, 19, 20, 21, 22 L / min, to ensure that the shielding gas flow rate is stable and evenly covers the welding area. Stable gas flow can form a uniform protective atmosphere and reduce defects caused by air entering the welding area.

[0078] Specifically, the specific process parameters of step S2 are: welding current is 310-340A, for example, 310, 315, 320, 325, 330, 335, 340A, welding voltage is 31-33V, welding speed is 40-44cm / min, and heat input is controlled at 14-16KJ / cm.

[0079] The process parameters in step S2 are designed according to the composition of the welding wire and the characteristics of the welding materials to optimize the welding quality and performance. The welding current and voltage directly determine the temperature and penetration of the molten pool, and match the melting characteristics of the alloy components such as Ni, Mn, and Cr in the welding wire to ensure a stable arc and sufficient penetration; the welding speed is controlled at 40-44 cm / min, the cooling rate of the molten pool is optimized, and the fine-grained strengthening elements such as Ti and V in the welding wire are combined to inhibit grain coarsening and improve the quality and toughness of the weld formation. The heat input is controlled within the range of 14-16 KJ / cm, which is a key parameter, which not only meets the needs of fully melting the parent material and the welding wire, but also avoids the problems of grain coarsening and cracking caused by excessively high molten pool temperature. Combined with Ni and Mo in the welding wire composition, this heat input range promotes the formation of fine and uniform ferrite and bainite structures in the weld, significantly improving the low-temperature toughness and impact resistance of the weld. In addition, reasonable heat input and cooling rate reduce welding stress concentration and reduce the probability of cold cracks and hot cracks. Through the optimization of the above parameters, combined with the welding wire composition, the performance advantages of the alloy elements in the welding wire can be fully utilized to form a stable weld structure with excellent strength, toughness and impact resistance. The entire process parameter design can meet the special needs of low-temperature and high-pressure equipment such as liquefied carbon dioxide storage tanks, ensuring the safety and reliability of welded joints in extreme environments.

[0080] Specifically, the post-weld treatment is performed by heat preservation and slow cooling. For example, heat preservation is performed directly after welding, and the heat preservation time is 2 to 6 hours, such as 2, 2.5, 3, 3.5, 4, 4.5, 5, 5.5, 6 hours, and then air cooling; no post-heat treatment is performed after welding, but a slow cooling method is used to control the cooling rate. Slow cooling can prevent the weld from becoming brittle and maintain a relatively fine grain structure, thereby improving the low-temperature toughness of the weld joint.

[0081] Specifically, the welding method is suitable for welding P690QL2 steel.

[0082] Furthermore, the welding method is suitable for the manufacture and maintenance of low-temperature and high-pressure equipment such as liquefied carbon dioxide storage tanks and LNG storage tanks, and is particularly suitable for full-pressure C-type double-ear liquid cargo tanks used in ship transportation.

[0083] Specifically, the weld metal microstructure formed by the welding method is ferrite and bainite, and the relative ratio (volume ratio) of the two is bainite: ferrite = 0.80-0.85: 0.15-0.20, and the grain size is 1.70-1.80 μm. More specifically, it is composed of acicular ferrite, side plate ferrite and granular bainite, with uniform tissue distribution and fine grains. The high proportion of bainite and the uniformly distributed ferrite together improve the strength and toughness of the weld, making it exhibit excellent performance in low-temperature impact tests. The fine-grained, multi-phase microstructure effectively disperses stress concentration, reduces the risk of brittle fracture, and significantly improves the overall mechanical properties of the weld joint.

[0084] Furthermore, the yield strength of the welded joint formed by the welding method is ≥792MPa, the tensile strength is ≥894MPa, and the elongation is ≥13.5%; the average absorbed energy of the -60°C impact test is ≥130.4J, and the joint hardness is 315-367HV.

[0085] Examples and Comparative Examples

[0086] The specific composition of the welding wire of each embodiment and comparative example is shown in Table 1.

[0087] Table 1 Specific composition of welding wire in various embodiments and comparative examples

[0088] C Si Mn Cr Ni Cu Mo V Ti Al Example 1 0.051 0.39 1.81 0.28 3.77 0.0097 0.0092 0.0006 0.055 0.013 Example 2 0.056 0.35 1.85 0.26 3.78 0.0089 0.0089 0.0007 0.054 0.014 Example 3 0.072 0.37 1.82 0.28 3.72 0.0092 0.0095 0.0006 0.055 0.015 Example 4 0.043 0.44 1.86 0.25 3.74 0.0094 0.0084 0.0007 0.054 0.014 Example 5 0.065 0.42 1.75 0.28 3.76 0.0092 0.0092 0.0007 0.056 0.015 Comparative Example 1 0.051 0.39 1.81 0.28 3.77 0.0097 0.0092 0.0006 0.055 0.013 Comparative Example 2 0.051 0.39 1.81 0.28 3.77 0.0097 0.0092 0.0006 0.055 0.013 Comparative Example 3 0.019 0.39 1.80 0.26 3.78 0.0092 0.0090 0.0005 0.051 0.012 Comparative Example 4 0.032 0.28 1.81 0.1 2.43 0.022 0.52 / 0.0064 /

[0089] The preparation processes of each embodiment and comparative example are as follows:

[0090] S21 ultra-pure smelting: double melting technology is used, first melting in an arc furnace, then refining in an induction furnace to further reduce the content of phosphorus (P) and sulfur (S). The refining temperature is controlled at 1650℃ for 2 hours, and the vacuum degree is maintained at no less than 10^-3Torr during the refining process.

[0091] S22 Forging and Rolling:

[0092] Forging process: First, the alloy is preheated to 950℃, and then forged at the initial forging temperature of 1200℃, and the temperature is controlled by gradual cooling technology. In the initial stage, a slower cooling rate (40℃ / h) is used to ensure the plasticity of the alloy and avoid cracks; the cooling rate is further reduced (30℃ / h and 15℃ / h) in the medium and low temperature stages to prevent grain coarsening and internal stress concentration. After forging, slow cooling is used until about 900℃.

[0093] Rolling process:

[0094] Rough rolling section: heating temperature 1120℃, the reduction of each rough rolling should be controlled between 25% and 35%, and the cooling rate is 50℃ / h;

[0095] Finishing rolling section: The temperature is maintained at 880±10℃, and the cooling rate is controlled at 15℃ / h to ensure grain refinement and uniform structure. During the finishing rolling process, the reduction of each finishing rolling should be controlled between 10% and 15% to maintain the surface quality of the alloy and optimize the mechanical properties. After the finishing rolling is completed, the welding wire rod is obtained.

[0096] S33 bright drawing: draw the welding wire rod, add lubricant during the drawing process (common commercially available high temperature resistant and high tensile lubricant can be used, no special requirements), and control the drawing speed at 6-8m / min.

[0097] S34 surface cleaning: Use highly absorbent microfiber cloth for mechanical wiping to improve cleaning efficiency. Perform ultrasonic cleaning after mechanical wiping, with an ultrasonic frequency of 40kHz and a cleaning time of 15 minutes.

[0098] The test plate material is P690QL2 steel plate, with specifications of 500mm long × 150mm wide × 20mm thick. A V-shaped groove is opened along the rolling direction of the test plate, and the groove gap is set to 16mm. The weld metal welding test is carried out. The specific welding process parameters are shown in Table 2.

[0099] Table 2 Welding process parameters of various embodiments and comparative examples

[0100]

[0101]

[0102] The mechanical properties and low-temperature toughness of the welds / welds of each embodiment and comparative example were tested, and the test results are shown in Table 3.

[0103] Table 3 Mechanical properties and low temperature toughness test results of each embodiment and comparative example

[0104]

[0105] In the detailed analysis of the embodiments and the comparative examples, the mechanical properties of the embodiments are significantly better than those of the comparative examples by precisely controlling the chemical composition and welding process parameters. The embodiments optimize the welding performance by adjusting the proportions of key elements such as carbon, silicon, nickel, and chromium, ensuring high strength and good low-temperature toughness. These adjustments have a direct impact on the microstructure and mechanical properties of the weld. Examples 3 and 5 in particular demonstrate how to refine the grain structure by increasing the carbon and aluminum content, thereby improving the overall performance, especially for applications in extreme environments. It is worth noting that the formula design of the welding wire ensures the lower limit of the welding performance of the welding method, and more preferred welding process parameters help to further give full play to the performance of the welding wire.

[0106] In contrast, the comparative examples demonstrate the performance limitations under non-optimized conditions. Although comparative examples 1 and 2 use the same basic alloy composition as the examples, they have different shielding gas ratios or increased heat input power, showing how these changes negatively affect the quality and performance of the weld. The poor shielding gas ratio in comparative example 1 leads to a relatively high level of impurities in the weld metal, resulting in reduced mechanical properties; the higher heat input in comparative example 2 leads to overheating of the weld zone, which may cause grain coarsening, which reduces the impact toughness of the weld, indicating the importance of controlling heat input.

[0107] In general, the comparison between the examples and the comparative examples emphasizes the key role of reasonable chemical composition and optimization of welding process parameters in achieving excellent welding performance. The composition optimization and welding parameter control of the examples ensure the high performance of the welded joints, while the performance limitations of the comparative examples highlight the necessity and effectiveness of the optimization of welding wire formula and process parameters.

[0108] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by any technician familiar with the technical field within the technical scope disclosed by the present invention should be covered within the protection scope of the present invention.

Claims

1. An efficient welding method, characterized in that: The welding method adopts a groove welding process, the welds of adjacent weld layers are in opposite directions, and the welds of the same weld layer are in the same direction; The welding method adopts a low-carbon low-alloy welding wire, wherein the components in the welding wire are calculated by mass percentage as follows: C 0.04-0.08%, Si 0.30-0.50%, Mn 1.6-2.0%, Cr 0.15-0.35%, Ni 3.5-4.0%, Cu 0.008-0.01%, Mo 0.007-0.01%, V 0.0005-0.001%, Ti 0.02-0.07%, Al 0.01-0.018%.

2. The welding method according to claim 1, characterized in that: The specific steps include: S1: Open the groove according to the material and specifications of the welded parts; S2: Use metal active gas shielded welding to perform stacking welding layer by layer. After each layer is welded, adjust the welding direction. The welding directions of adjacent welding layers are opposite, and the welding directions of the same welding layer are the same. S3: After welding is completed, post-weld treatment is performed.

3. The welding method according to claim 2, characterized in that: The welded parts are preheated before welding, and the preheating temperature is 100-120°C; the interpass temperature is controlled at 100-120°C during the welding process.

4. The welding method according to claim 2, characterized in that: The volume ratio of the shielding gas for MAG welding in step S2 is 95% argon + 5% carbon dioxide.

5. The welding method according to claim 4, characterized in that: The flow rate of the protective gas is controlled at 18-22 L / min.

6. The welding method according to claim 2, characterized in that: The specific process parameters of step S2 are: welding current is 310-340A, welding voltage is 31-33V, welding speed is 40-44cm / min, and heat input is controlled at 14-16KJ / cm.

7. The welding method according to claim 2, characterized in that: The post-weld treatment is carried out by heat preservation and slow cooling.

8. The welding method according to claim 1, characterized in that: The welding method is suitable for welding P690QL2 steel.

9. The welding method according to claim 1, characterized in that: The weld metal microstructure formed by the welding method is ferrite and bainite; the ratio of the two is bainite:ferrite=0.80-0.85:0.15-0.20, and the grain size is 1.70-1.80 μm.

10. The welding method according to claim 1, characterized in that: The welded joint formed by the welding method has a yield strength of ≥792MPa, a tensile strength of ≥894MPa, and an elongation of ≥13.5%; an average absorbed energy of a -60°C impact test is ≥130.4J, and a joint hardness of 315-367HV.

Citation Information

Patent Citations

  • Welding material, weld metal and application

    CN103480985A

  • Welding method for Q690 high-strength steel tube of ultra-high voltage power transmission steel tube tower

    CN104057186A

  • Advanced pass progression for build-up welding

    CN104245221A

  • 785MPa-class high-strength and high-ductility consumable electrode active gas-shielded welding wire used for marine engineering and application thereof

    CN110802344A

  • Flux-cored wire, welded metal, gas-shielded arc welding method, and method for manufacturing welded joint

    CN114850627A